Aging and body composition in women who took part in a a council programme on physical practice - B. Tabernero; J. G. Villa; J. García; S. Márquez (Asociación Española de Ciencias del Deporte, 2010)
The objective of the present study was to develop a percentile scale according to age for the specific evaluation of body composition (since it is a component of physical condition related to health) and to quantify the variation in body composition for the different age groups. A total of 890 women enrolled in the municipal program for physical exercise were measured according to the directives of the Spanish Group of Kineanthropometry. The results show a progressive increase with age in body weight and fat mass as well as a decrease in height. A percentile scale according to age was also elaborated for diverse parameters of body composition. Likewise, the diversity of generalised equations used for estimating percentage of body fat was noted, thus confirming that a more objective evaluation, such as the index determined by the sum of skin folds, would be more suitable.